Fragments of Broken History: Misrepresentations of Dahomey in Contemporary Culture - Ron Lawrence Anderson (IAFOR Journal of Cultural Studies)
As a discipline, history has only been introduced into Africa relatively recently, and there are still many challenges when researching the African past. The pre-colonial kingdom of Dahomey on West Africa’s Guinea Coast, today part of the Benin Republic, has a documented history based overwhelmingly on accounts from slave traders and colonial administrators, or other questionable sources. This has helped to create inverted historical narratives about the region and its peoples—sometimes favouring European perspectives over African ones, and sometimes emphasizing false stories built into local oral traditions. However, history as a disciple offers greater clarity over time, since the past is continually being re-assessed and refined with new evidence. Consequently, in modern times many errors have been corrected through dedicated research by historical specialists. Unfortunately, at the same time popular media – the internet, cinema and street art among them – continue to compound errors still in the historical record, and often even introduce new ones. The chasm between popular and academic perspectives on Dahomey seems to be widening. This article explores the dangers presented by the unvetted historical impressions conveyed through contemporary culture and popular art. It does so by contrasting informed academic knowledge with popular perspectives on the kingdom, mostly conveyed through mass media—both within the Republic of Benin, and around the world.